2013
DOI: 10.4028/www.scientific.net/amm.351-352.1368
|View full text |Cite
|
Sign up to set email alerts
|

Test on Slip Coefficient of High-Strength Bolted Slip-Critical Connections after Fire

Abstract: Fire safety is a major concern with steel structures. Actually, steel structures were not fatally destroyed in most cases of fire. These damaged steel structures may be reused after structural inspection, safety appraisal and necessary repair. Bolted connections are the most widely used connection in steel structures. Slip coefficient is a key parameter to calculate the slip bearing capacity of bolted slip-critical connections. Currently there are few research results available about slip coefficient of bolted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Król and Wachowski [7] found that the temperature level of the fre, fre duration, and fre-fghting method signifcantly afect the bolts' mechanical properties. Lange and González [8], Lou et al [9], and Zhu et al [10] studied the mechanical properties, slip coefcient, and pretension force of high-strength grade 10.9 bolts at high temperatures. Hanus et al [11] investigated the mechanical behavior of high-strength grade 8.8 bolts under the situation of "nature fre," which means a temperature history including both heating and cooling phases.…”
Section: Introductionmentioning
confidence: 99%
“…Król and Wachowski [7] found that the temperature level of the fre, fre duration, and fre-fghting method signifcantly afect the bolts' mechanical properties. Lange and González [8], Lou et al [9], and Zhu et al [10] studied the mechanical properties, slip coefcient, and pretension force of high-strength grade 10.9 bolts at high temperatures. Hanus et al [11] investigated the mechanical behavior of high-strength grade 8.8 bolts under the situation of "nature fre," which means a temperature history including both heating and cooling phases.…”
Section: Introductionmentioning
confidence: 99%